2005
DOI: 10.1126/science.1112699
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Resistance via Transposition-Mediated Adaptive Gene Truncation in Drosophila

Abstract: To study adaptation, it is essential to identify multiple adaptive mutations and to characterize their molecular, phenotypic, selective, and ecological consequences. Here we describe a genomic screen for adaptive insertions of transposable elements in Drosophila. Using a pilot application of this screen, we have identified an adaptive transposable element insertion, which truncates a gene and apparently generates a functional protein in the process. The insertion of this transposable element confers increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
243
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(259 citation statements)
references
References 16 publications
12
243
2
2
Order By: Relevance
“…In the case of divergence, applications of the McDonald-Kreitman test to multiple-gene data sets from Drosophila have concluded that up to 60% of nonsynonymous substitutions and 30% of the substitutions at regulatory sites may be driven by adaptation (Fay et al 2002;Smith and Eyre-Walker 2002;Bierne and Eyre-Walker 2004;Andolfatto 2005;Charlesworth and Eyre-Walker 2006;Welch 2006;Shapiro et al 2007). In the case of polymorphism, the effects of adaptation have also been seen in Drosophila: selective sweeps, which are local reductions in linked neutral polymorphism caused by adaptive substitutions, have been repeatedly detected in Drosophila populations, both in detailed studies of individual loci (e.g., Schlenke and Begun 2004;Aminetzach et al 2005;Beisswanger et al 2006) and in genomic scans (e.g., Glinka et al 2003;Orengo and Aguade 2004;Ometto et al 2005).…”
Section: P Atterns Of Genetic Variation Within and Betweenmentioning
confidence: 99%
“…In the case of divergence, applications of the McDonald-Kreitman test to multiple-gene data sets from Drosophila have concluded that up to 60% of nonsynonymous substitutions and 30% of the substitutions at regulatory sites may be driven by adaptation (Fay et al 2002;Smith and Eyre-Walker 2002;Bierne and Eyre-Walker 2004;Andolfatto 2005;Charlesworth and Eyre-Walker 2006;Welch 2006;Shapiro et al 2007). In the case of polymorphism, the effects of adaptation have also been seen in Drosophila: selective sweeps, which are local reductions in linked neutral polymorphism caused by adaptive substitutions, have been repeatedly detected in Drosophila populations, both in detailed studies of individual loci (e.g., Schlenke and Begun 2004;Aminetzach et al 2005;Beisswanger et al 2006) and in genomic scans (e.g., Glinka et al 2003;Orengo and Aguade 2004;Ometto et al 2005).…”
Section: P Atterns Of Genetic Variation Within and Betweenmentioning
confidence: 99%
“…Sequences derived from TEs constitute a substantial fraction of genomes of most eukaryotes and the presence or absence of various TE families as well as their distributions among individuals of the same species are well documented in model species such as Drosophila melanogaster, Caenorhabditis elegans, Arabidopsis thaliana, Mus musculus as well as Homo sapiens. Even though researchers have found examples of TE insertions correlated with positive selective sweeps in specific environments (Daborn et al 2002;Aminetzach et al 2005), the great majority of TE insertions have negative impact on host fitness (Mackay 1989;Pasyukova et al 2004) and are widely viewed as 'genomic parasites'. TE insertions in or near genes often change gene expression that result in phenotypic changes of the hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Common examples include insertional inactivation of genes (Greene et al 1994) and DNA rearrangement via ectopic recombination (Kazazian 2004;Bennetzen 2005). Nonetheless, a subset of TE-mediated events is adaptive: in Drosophila, for example, TE insertions have contributed to enhanced insecticide resistance, either by affecting gene expression or by changing gene structure (Schlenke and Begun 2004;Aminetzach et al 2005). Similarly, a ''domesticated'' TE-derived transposase domain contributed directly to two vertebrate proteins, RAG1 and RAG2, that are central to the immune system of jawed vertebrates (Kapitonov and Jurka 2005).…”
Section: Introductionmentioning
confidence: 99%